2016
DOI: 10.1155/2016/9647675
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Assay Performance of Commercial Hepatitis E Virus Enzyme-Linked Immunosorbent Assay Kits in Australian Blood Donor Samples

Abstract: Hepatitis E virus (HEV) is transfusion-transmissible and therefore poses a risk to blood transfusion safety. Seroprevalence studies are useful for estimating disease burden and determining risk factors. Considerable variability in the sensitivity of HEV antibody detection assays exists. This study aimed to compare the performances of commercially available HEV enzyme-linked immunosorbent assays (ELISA) in Australian blood donor samples. Plasma samples that tested positive (n = 194) or negative (n = 200) for HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…[16][17][18] The performance of anti-HEV IgG assays may have played a role in the higher seroprevalence of anti-HEV antibodies found in recent studies. 19 Two different studies, both in blood donors, one in Southern Brazil (10%) and other in Southeastern Brazil (9.8%) found similar prevalence to that reported in this study. 17,18 Both of them used the same high sensitivity commercial anti-HEV assays contributed to the similar detection of anti-HEV rates to those observed in this study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…[16][17][18] The performance of anti-HEV IgG assays may have played a role in the higher seroprevalence of anti-HEV antibodies found in recent studies. 19 Two different studies, both in blood donors, one in Southern Brazil (10%) and other in Southeastern Brazil (9.8%) found similar prevalence to that reported in this study. 17,18 Both of them used the same high sensitivity commercial anti-HEV assays contributed to the similar detection of anti-HEV rates to those observed in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Currently, data about seroprevalence of HEV infection in Brazil are improving and showing increase of the prevalence . The performance of anti‐HEV IgG assays may have played a role in the higher seroprevalence of anti‐HEV antibodies found in recent studies . Two different studies, both in blood donors, one in Southern Brazil (10%) and other in Southeastern Brazil (9.8%) found similar prevalence to that reported in this study .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Additionally, studies have indicated that commercially Journal of Pathogens 3 available ELISA kits for anti-HEV antibodies differ dramatically in their sensitivity and specificity [34][35][36]. In our study, we used an ELISA kit that has been confirmed to have the highest diagnostic sensitivity and specificity when compared to many others by several studies [35,37].…”
Section: Discussionmentioning
confidence: 92%
“…6 Subsequent studies from Germany, France, Korea, and Australia comparing different enzyme-linked immunosorbent assay (ELISA) kits confirmed the higher sensitivity of the Wantai assay. [7][8][9][10][11][12] In this study, new generation serological assays (Wantai, Beijing, China and Dia.Pro, Milan, Italy) utilizing total anti-HEV antibodies (Ab) based on HEVlike particles, including anti-HEV IgG, immunoglobulin M (IgM) and…”
Section: Introductionmentioning
confidence: 99%